Business model innovation and decision making: uncovering mechanisms for coping with uncertainty - Schneckenberg, Dirk; Velamuri, Vivek K.; Comberg, Christian; Spieth, Patrick (R & D management, 2017)
As a research subject, business model innovation spans the strategy, innovation, and entrepreneurship fields. Yet, despite the importance of the concept, prior work has paid little attention to how decision‐makers cope with uncertainty and gain understanding about interdependencies in new business model configurations. To address this gap, we combine top‐down theorising and evidence‐based exploration and seek to unpack some of the coping mechanisms that operate in the evolutionary view of business model innovation. Using in‐depth interviewing to collect data, our study reveals five strategies – customer centricity, value co‐creation, capability evolution, ecosystem growth, and adaptive pricing – that decision‐makers apply to cope with uncertainty in business model innovation. We find that coping mechanisms support decision making during the development of new business models. Furthermore, we find that the five coping strategies delineate decision making for value proposition, value creation, and value capture configurations in more detail than existing literature has described. Our findings have important implications for decision making in business model innovation.